130k views
0 votes
How do I solve for g when 5q=h*2(-N+g)

User Chaochana
by
5.5k points

1 Answer

5 votes

Answer:

(5q/2h) + N = g

Explanation:

Correct me if I'm wrong but what you have is equivalent to the following?

5q = 2h(-N + g)

5q/2h = -N + g (divide by 2h on both sides)

(5q/2h) + N = g (add N to both sides)

This isolates g.

Hope this helps :)

User Zhanna
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.